2021
DOI: 10.3389/fpubh.2021.755391
|View full text |Cite
|
Sign up to set email alerts
|

Timely Communication Through Telehealth: Added Value for a Caregiver During COVID-19

Abstract: Objective: This caregiver case study applies the lens of relational coordination theory (RC) to examine the value of telehealth as a medium of care coordination for a pediatric patient with hypermobile Ehlers-Danlos Syndrome (hEDS) during the COVID-19 pandemic.Background: The COVID-19 pandemic has placed an unprecedented burden on the delivery of healthcare around the globe and has increased the reliance on telehealth services. Delivering telehealth requires a high level of communication and coordination withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…O atendimento virtual no CPP aumentou significativamente com a propagação do SARS-CoV-2 pelo mundo, passando a ser usado para minimizar os danos decorrentes do isolamento social. Segundo Hajjar;Kragen (2021), o uso dos teleatendimentos trouxe inúmeros benefícios, como a economia de tempo com a locomoção, a flexibilização dos horários, o aumento do número de consultas e o maior acesso aos profissionais especialistas. Entretanto, apesar desses ganhos, os profissionais relataram que a visão bidimensional das telas impedia a avaliação completa do doente, já que não era possível contemplar a linguagem corporal, fazer o exame físico e triar a capacidade motora.…”
Section: Resultsunclassified
“…O atendimento virtual no CPP aumentou significativamente com a propagação do SARS-CoV-2 pelo mundo, passando a ser usado para minimizar os danos decorrentes do isolamento social. Segundo Hajjar;Kragen (2021), o uso dos teleatendimentos trouxe inúmeros benefícios, como a economia de tempo com a locomoção, a flexibilização dos horários, o aumento do número de consultas e o maior acesso aos profissionais especialistas. Entretanto, apesar desses ganhos, os profissionais relataram que a visão bidimensional das telas impedia a avaliação completa do doente, já que não era possível contemplar a linguagem corporal, fazer o exame físico e triar a capacidade motora.…”
Section: Resultsunclassified
“…Family caregivers and care recipients in LTC facilities experienced the impacts of the COVID-19 pandemic, such as physical contact restrictions and limited interactions. 53,55,[95][96][97][98] As such, the pandemic accelerated the adoption and diffusion of new technologies in health care. 18 Mobile technologies can minimize the risk of exposure to COVID-19 and serve as alternative ways to communicate with the care recipient and LTC staff.…”
Section: Discussionmentioning
confidence: 99%
“…7,51,52 The coronavirus disease of 2019 (COVID-19) pandemic highlighted the potential of mobile technologies to support the communication and interactions of LTC recipients with family caregivers 53 and reduce isolation. [53][54][55][56][57][58] Studies have identified that perceived usefulness and familiarity with the technology can promote the adoption of mobile technologies. 37,59 This paper is a subsequent phase of a more extensive study conducted to explore a mobile app's technology acceptance and usability.…”
Section: Background and Significancementioning
confidence: 99%
“…With social distancing becoming an essential method of COVID-19 prevention, telemedicine and telehealth possibly become the ideal communication methods between caregivers and patients[ 73 ]. There has been a flood of videoconferences, "live presentations" in social networks, online training classes on online learning platforms, telepractice concerning different fields such as psychiatry, psychology, occupational therapy, speech therapy, and other remote activities that offer support, guidance, and treatment when applicable.…”
Section: Indirect Impact Of Covid-19mentioning
confidence: 99%